Risk factors associated with complications/sequelae of acute and subacute haematogenous osteomyelitis: an Italian multicenter study. Issue 4 (3rd April 2018) - Chiappini, Elena; Krzysztofiak, Andrzej; Bozzola, Elena; Gabiano, Clara; Esposito, Susanna; Lo Vecchio, Andrea; Govoni, Maria Rita; Vallongo, Cristina; Dodi, Icilio; Castagnola, Elio; Rossi, Nadia; Valentini, Piero; et al.
ABSTRACT: Background : Acute/subacute haematogenous osteomyelitis (AHOM/SAHOM) are potentially devastating diseases. Updated information about the epidemiology, management and outcome of AHOM/SAHOM is needed to minimize the risk of complications and sequelae. Methods : A multicenter study was performed to evaluate retrospectively the management and outcome of AHOM/SAHOM in Italy. Data from children aged >1 month, and hospitalized between 2010 and 2016, in 19 pediatric centers, were analyzed. Results : 300 children with AHOM and 98 with SAHOM were included. Median age was 6.0 years (IQR: 2.0–11.0). No clinical difference was observed with the exception of fever at onset (63.0% vs . 42.9%; P < 0.0001), and a more common spinal involvement in SAHOM (6.7% vs 20.4%; P < 0.001). Fifty-Eight Staphylococcus aureus strains were isolated; 5 (8.6%) were MRSA. No Kingella kingae infection was documented. No different risk for complication/sequela was observed between AHOM and SAHOM (38.3% vs . 34.7%; OR:0.85; 95%CI: 0.53–1.38; P = 0.518). Duration and type of antibiotic therapy were not associated with risk of complication/sequelae. Conclusion : AHOM and SAHOM displayed some differences, however occurrence and risk factors for complications and sequelae are similar, and the same empiric treatment might be recommended.